LEARNING MODEL OPTIMIZATION TEACHER-CENTERED LECTURE METHOD CASE STUDY (INTERNATIONAL SEMINAR, 2024)
Optimizing a learning model that focuses on teachersis an effort to improve the quality of the teaching and learningprocess by emphasizing the main role of teachers in transferringknowledge to students. One method commonly used in thisapproach is a lecture, where the material is presented orally by theeducator. This research aims to identify factors that influence theeffectiveness of the lecture method in teacher-oriented learning,as well as propose strategies to optimize this method. This casestudy was conducted at the university education level, where theanalysis focuses on the interaction between educators andstudents during the lecture process, as well as its impact onstudents' understanding of the material received. The researchresults show that factors such as teaching style, use of visual aids,and variations in material delivery play an important role inincreasing students' attention and understanding. Therefore, tooptimize the lecture method in a teacher-focused learning model,it is necessary to increase teacher skills in managing the class andutilizing various learning media. This aims to create a moredynamic and interesting atmosphere for students. This researchalso recommends training for teachers to master more effectivelecturing techniques and emphasizes the importance ofcontinuous evaluation of the teaching strategies implemented.